2008
DOI: 10.1007/s12034-008-0052-y
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio studies on [bmim][PF6]-CO2 mixture and CO2 clusters

Abstract: Ab initio molecular dynamics studies have been carried out on the room temperature ionic liquid, 1,n-butyl,3-methylimidazolium hexafluorophosphate ([bmim][PF 6 ]) and supercritical carbon dioxide mixture at room temperature and experimental density. Partial radial distribution functions (RDF) for different sites have been computed to see the organization of CO 2 molecules around the ionic liquid. Several partial RDFs around the carbon atom of CO 2 molecule are compared to find out that the CO 2 has specific in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 63 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…54,[103][104][105][106][107][108] Up to now, most work has focused on [PF 6 ] and [Tf 2 N] anions, paired with imidazolium-based cations. 54,66,105,[109][110][111][112][113] For example, the reason for the partial molar volume of CO 2 being so small when dissolved in [bmim] [PF 6 ] was investigated by molecular dynamics simulations. It was found that most of the spaces occupied by CO 2 in the ionic liquids are larger cavities rather than those already existing in the pure ionic liquids.…”
Section: Conventional Ionic Liquidsmentioning
confidence: 99%
“…54,[103][104][105][106][107][108] Up to now, most work has focused on [PF 6 ] and [Tf 2 N] anions, paired with imidazolium-based cations. 54,66,105,[109][110][111][112][113] For example, the reason for the partial molar volume of CO 2 being so small when dissolved in [bmim] [PF 6 ] was investigated by molecular dynamics simulations. It was found that most of the spaces occupied by CO 2 in the ionic liquids are larger cavities rather than those already existing in the pure ionic liquids.…”
Section: Conventional Ionic Liquidsmentioning
confidence: 99%
“…[83][84][85][86][87][88][89][90][91][92] Only a few AIMD studies of solute ILs mixtures were reported up to now. [93][94][95][96] In our investigation, we will study the influence of a small amount of water in mono-methylammonium nitrate (MMAN) on the IL and the change of the properties of water by this solvation. Previous studies of pure protic ammonium-based ILs and pure water have highlighted similar properties for both liquids.…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 molecule in supercritical phase shows unique characteristics of liquid-like density and gas-like diffusivity in addition to its nontoxic behaviour, as observed in neutron diffraction experiments. [14][15][16] It has been observed in some earlier studies that, due to close proximity of the monomers in these dense phases, the CO 2 molecules no longer remain linear, [17][18][19][20] giving rise to instantaneous dipole moment. Thus we believe, which can be understood in the light of their linear and nonlinear optical response functions.…”
Section: Introductionmentioning
confidence: 93%
“…We have arranged several single molecular optimized structures in different special orientations and optimized further the molecular aggregates to obtain the cluster geometry, which can be seen possibly in dense CO 2 phases like supercritical one. [17][18][19] The calculated binding energies for these molecular assemblies are given in table 1. As can be seen, the dimer with slipped parallel geometry (D1) is slightly stabler than the T-shape one (D2).…”
Section: Structure and Geometrymentioning
confidence: 99%